Influence of Micrometric-Scale Electrode Heterogeneity on Electrochemical Impedance Spectroscopy. (20th May 2016) - Alexander, Christopher L.; Tribollet, Bernard; Orazem, Mark E.
Abstract : Highlights: Frequency at which time-constant dispersion appears depends on a characteristic dimension. Distributions of charge–transfer resistance do not cause time–constant dispersion. Roughness, capacitance distributions, or charge–transfer resistance distributions cannot explain observed CPE behavior. Abstract: Numerical simulations for a disk electrode show that the frequency at which time–constant dispersion appears depends on the characteristic dimension of the feature causing the dispersion. The characteristic dimension for a disk is the radius; for roughness, it is a function of rugosity and the period of the roughness; and for a capacitance distribution, it is the period of the distribution. Distributions of charge–transfer resistance do not cause time–constant dispersion because they influence neither the ohmic resistance nor the capacitance. As only the high–frequency impedance is affected by roughness and capacity distributions and charge–transfer resistance distributions do not cause frequency dispersion, surface heterogeneity in the form of roughness, capacitance, or charge–transfer resistance cannot provide an explanation for CPE behavior associated with surface distributions.